Incidence of injury in elite junior Rugby Union: a prospective descriptive study - McManus, Alexandra; Cross, D. (Sports Medicine Australia, 2004)
The high incidence of injury in Rugby Union is well documented, particularly at elite levels of competition. This article describes the incidence and nature of all injuries sustained by elite Western Australian junior Rugby Union players during the 26 weeks up to and including the 1997 National Championship campaign. Informed consent was gained for each participant (n=44) prior to completion of an extensive baseline questionnaire. Exposure and injury data were collected at each training session and game. The injury incidence rate over the 26 week period was 13.26/1000 player hours. Injury data were analysed by phase of play, position, severity and if occurred at games or training. The incidence of injury was significantly associated with the position played (X2 = 67.49, p value = 0.008) and the phase of play in which the injury occurred (X2 = 8.07, p value = 0.042). Tackling was the most dangerous phase of play (52% of injuries) and the most common site of injury was the lower limb (37%). Most injuries occurred during games (56%) and the flanker was the position most at risk of injury (12%).Further research is needed to identify the aetiology of injury at all levels of competition and to use these findings to develop effective injury prevention strategies in this sport. Positionspecific risk factors should also be investigated, as should the mechanism of injury associated with tackling which is the phase of play in which significantly more injuries occur in rugby.